Tembang Dolanan Anak-anak - Sri Hesti Heriwati (Gelar : Jurnal Seni Budaya, 2007)
consciouslY makes every effort to express the sense. One can find an outlet for his  estbetic sense through various kinds of means or media. A literary man will express  his estbetic sense through a means of language. A language is something that is not  separable from human lift. Children understand the realz!J around them, make  social interaction and describe the reality again using a language. Tembang dolanan.  a work of art with which children familiar, is an author's work containing estbetic  values.A literary text is a whole systemic unit of language taken the shape of oral  or writing utterance. A text specifically  refers to a unit syntacti« or semantic strudllre  which coherentlY creates interrelated relations so it makes a full message/ injormation.  A literary text contained in children bembang dolanan is possible to be anaIYzed  from ma'!Y aspects depending on the study. In relation to the above problems, the  discourse of children's tembang dolanan will be closelY studied grammaticallY and  lexicallY.Keywords: Tembang (recited Javanese Poetry), discourse,  grammatical, lexical.